2022
DOI: 10.1001/jamaneurol.2022.3031
|View full text |Cite|
|
Sign up to set email alerts
|

Severity and Etiology of Incident Stroke in Patients Screened for Atrial Fibrillation vs Usual Care and the Impact of Prior Stroke

Abstract: IMPORTANCE Atrial fibrillation (AF) screening trials have failed to demonstrate a significant reduction in stroke risk. The impact on stroke severity and the importance of prior strokes are unknown.OBJECTIVE To assess stroke characteristics in patients undergoing implantable loop recorder (ILR) screening for AF vs usual care and assess the importance of prior stroke. DESIGN, SETTING, AND PARTICIPANTSThis was a post hoc analysis of the Atrial Fibrillation Detected by Continuous Electrocardiogram Monitoring Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…4 Contraindications ILR implantation is contraindicated when there is no indication for its use, the patient has an active infection, or when a patient has an uncorrected bleeding disorder. [5][6][7][8] Post-procedure ILR patient education 5…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Contraindications ILR implantation is contraindicated when there is no indication for its use, the patient has an active infection, or when a patient has an uncorrected bleeding disorder. [5][6][7][8] Post-procedure ILR patient education 5…”
Section: Indicationsmentioning
confidence: 99%
“…7 The control group had more bleeding episodes, accounting for 156 compared with 65 in the ILR group. 8 The researchers concluded that ILR screening resulted in a three-times increase in AF detection and anticoagulation initiation in individuals with stroke risk factors but no significant reduction in the risk of stroke or systemic arterial embolism. The researchers further stated that their findings might imply that it is not worth screening for all AF and that not all screen-detected AF merits anticoagulation.…”
Section: Wound Carementioning
confidence: 99%
See 1 more Smart Citation
“…33 On the other hand, a post hoc randomized clinical trial of implantable loop recorder (ILR) screening for AF vs. usual care in individuals aged !70 years with risk factors did not find a significant reduction in disabling or lethal stroke; while cardioembolism was relatively rare, observed strokes were ischemic, mostly due to small-vessel disease, and AF detection by ILR was associated with more severe events compared with the undetected ones. 34 Current recommendations on AHREs detected by implanted devices are to consider them as innocent bystanders when they are of short duration and occur in patients with low/intermediate TEE risk. On the other hand, AHREs longer than 24 h in high TEE risk patients would recommend starting anticoagulation; in any event, closer follow-up visits for AF development are mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…The Original Investigation “Severity and Etiology of Incident Stroke in Patients Screened for Atrial Fibrillation vs Usual Care and the Impact of Prior Stroke: A Post Hoc Analysis of the LOOP Randomized Clinical Trial,” published online August 29, 2022, had an error in the Statistical Analysis section of the text. The cutoff for statistical significance should read P < .05 rather than P > .05.…”
mentioning
confidence: 99%